Antecedent factors in different types of workplace violence against nurses: A systematic review. (January 2019) - Nowrouzi-Kia, Behdin; Isidro, Rachelle; Chai, Emily; Usuba, Koyo; Chen, Amy
Abstract: Aim The purpose of this systematic review is to identify the antecedent factors in different types of workplace violence (WPV) against nurses and understand its impact in order to promote safe working conditions in health care. Background: Currently, the evidence examining antecedent factors associated with workplace violence in nursing is restricted to cross-sectional studies and a somewhat heterogeneous subject matter, thus confining the inferences that are possible. In healthcare, workplace violence towards nurses is a growing and serious public health issue and occupational hazard. Methods: Primary papers on workplace violence in nursing were identified through a literature search in four health databases (Ovid Medline, Embase, PsychoINFO and CINAHL), using a systematic review protocol tailored to each database. After the finalization of all search strategies, another health librarian searched on November 29th, 2016, as well as an updated search on August 29th, 2017.The Critical Appraisal Skills Programme (CASP), and the Cochrane Collaboration 'Risk of bias' assessment tools were used to assess study quality. Results The study identified a total of 3309 articles before the removal of duplicate records. The mean CASP score was 8.14(±1.29) out of a total score of 10. Antecedent factors of workplace were grouped into two categories of WPV: Type II (patient/client) and Type III (worker-on-worker)." Discussion: The antecedent factors identified the studies need to be developed and implemented into intervention studies. Furthermore such studies need to be rigorously evaluated through a meta-analytic approach to develop robust solutions and offer recommendations to nurses and workplaces. Implications for nursing & health policy: The identified antecedent factors build on the existing evidence related to workplace violence. This systematic review supports the need for intervention-based organizational and state level policies that are evidence-based to mitigate or prevent workplace violence among nurses.